Analysis Of Mother's Role Regarding Dental Health And The Incident Of Dental Careies In Preschool Children At Rukun Ibu Kindergarten, Tuban District - Ni Komang Ayu Muliartini; Katmini (Universitas STRADA Indonesia, 2019)
Background: Preschool children like to try new foods, especially foods that contain high sugar, this causes dental problems in the form of dental caries. Mothers have a very important role in maintaining the health of their children's teeth. Research Objective: to analyze the role of mothers regarding dental health in the incidence of children's dental caries in preschool children at Rukun Ibu Kindergarten, Tuban Regency. Research Method: The research design used cross sectional analysis with a sample size of 35 respondents from a total population of 40 respondents at Rukun Ibu Kindergarten, Tuban Regency. The sampling technique uses simple random sampling. This research was carried out from May 2019 to January 2020. Research data was collected using; def-t questionnaire and observation sheet. Data completion with; editing data processing, coding, scoring and tabulation. Data were processed using the SPSS 22 program with the Pearson correlation test. Results: The results of data processing for the independent variable (Mother's Role) showed that 25 (71%) respondents played a positive role while 10 (29%) respondents played a negative role. The results of observations of the dependent variable (dental caries) showed that the majority of respondents had the Very Low (VL) dental caries category, namely 27 (77.2%) respondents, the Low (L) category was 2 (5.7%) respondents, the Medium Category ( M) was 2 (5.7%) respondents, High Category (H) was 2 (5.7%) respondents and Very High Category (VH) was 2 (5.7%) respondents. The results of the regression analysis of the significance of two variables show a value of 0.00 <α (0.05) which proves that the hypothesis is accepted. The Pearson correlation test on the two variables produced a figure of -0.574, meaning that there is a significant and inverse relationship between the mother's role and the incidence of dental caries. Conclusion: The mother's role has a big influence on children's dental health. Statistical results show that; The better the quality of the mother's role, the lower the incidence of dental caries in children. It is highly recommended to provide guidance, education and training to mothers regarding maintaining children's dental health.